2019
DOI: 10.3390/nano9081150
|View full text |Cite
|
Sign up to set email alerts
|

Design of Nanoscaled Surface Morphology of TiO2–Ag2O Composite Nanorods through Sputtering Decoration Process and Their Low-Concentration NO2 Gas-Sensing Behaviors

Abstract: TiO2–Ag2O composite nanorods with various Ag2O configurations were synthesized by a two-step process, in which the core TiO2 nanorods were prepared by the hydrothermal method and subsequently the Ag2O crystals were deposited by sputtering deposition. Two types of the TiO2–Ag2O composite nanorods were fabricated; specifically, discrete Ag2O particle-decorated TiO2 composite nanorods and layered Ag2O-encapsulated TiO2 core–shell nanorods were designed by controlling the sputtering duration of the Ag2O. The struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…The n-type gas-sensing behavior of the ZnO-NiO porous sheets exposed to the ethanol vapor herein demonstrated that the NiO crystallites are not fully covered the whole surfaces of the porous ZnO nanosheet template. This is similar to the gas-sensing behavior in the TiO 2 –Ag 2 O composite nanorods with p-type Ag 2 O crystallite decoration not fully covered the surfaces of the TiO 2 nanorod templates [ 3 ]. The exposure of the surfaces of the n-type templates in the composite structure might affect the electric properties of the p-n composite structure during reducing gas-sensing tests.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The n-type gas-sensing behavior of the ZnO-NiO porous sheets exposed to the ethanol vapor herein demonstrated that the NiO crystallites are not fully covered the whole surfaces of the porous ZnO nanosheet template. This is similar to the gas-sensing behavior in the TiO 2 –Ag 2 O composite nanorods with p-type Ag 2 O crystallite decoration not fully covered the surfaces of the TiO 2 nanorod templates [ 3 ]. The exposure of the surfaces of the n-type templates in the composite structure might affect the electric properties of the p-n composite structure during reducing gas-sensing tests.…”
Section: Resultssupporting
confidence: 75%
“…The thick p-type oxide coverage layer might reduce the p-n junction thickness variation sensitivity in the p-n oxide heterostructures on exposure before and after to target gases. For example, in one-dimensional TiO 2 -Ag 2 O p-n heterogeneous system, too thick Ag 2 O coverage layer on TiO 2 nanorods further decreases the gas-sensing performance of the TiO 2 -Ag 2 O nanorods [ 3 ]. Based on the aforementioned possible reasons, the ZnO-NiO-2 sensor showed inferior ethanol vapor sensing performance than that of the ZnO-NiO-1 sensor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, compared with the n-type gas-sensing behavior of pristine TiO 2 , the gas-sensing behavior of TiO 2 -NiO composites changes to p-type due to the p-type nature of NiO shells. In p-n oxide composites having a homogeneous p-type shell layer coverage, the gas-sensing behavior is dominated by p-type shell layers [6,34]. The possible difference in the gas-sensing ability of the NST and NPT might be associated with surface defect density differences.…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 has been widely studied for applications in photodegradation organic dyes and gas-sensing materials because of its low toxicity, high chemical stability, and environmental friendliness [1][2][3][4][5][6]. However, TiO 2 still has some drawbacks that might limit its efficiency in photocatalyst and gas-sensing materials.…”
Section: Introductionmentioning
confidence: 99%